Oscilações Holocênicas do Nível Relativo do Mar Registradas na Sucessão de Fácies Lagunares na Região da Laguna de Tramandaí, RS. - DILLENBURG, SERGIO (Pesquisas em Geociências, 1996)
Analysis of lagoonal facies within the area of Tramandaí lagoon, Southern Brazil, has provided information concerning relative sea level behavior during the Holocene that is applicable to other areas in Brazil where indicators of ancient sea levels are not available. The record of a first coastal submergence, between 6,730 and 5,000 years BP, followed by a general recession of the sea level until the present day, is in good agreement with data from other regions of the Brazilian coast. A possible second coastal submergence, at about 1,820 years BP, still needs more investigation.